A randomized controlled trial of neuromuscular electrical stimulation for chronic urinary retention following traumatic brain injury. Issue 2 (January 2019) - Zhang, Yong-bing; Cheng, Yan-na
Abstract: Background: This study aimed to evaluate the effectiveness of neuromuscular electrical stimulation (NMES) therapy for chronic urinary retention (CUR) following traumatic brain injury (TBI). Methods: This 2-arm randomized controlled trial (RCT) enrolled 86 eligible patients with CUR following TBI. All included patients were randomly allocated to a treatment group (n = 43) or a sham group (n = 43). The administration of NMES or sham NMES, as intervention, was performed for an 8-week period treatment, and 4-week period follow-up. In addition, all subjects were required to undergo indwelling urinary catheter throughout the study period. The primary outcome was assessed by the post-voiding residual urine volume (PV-VRU). The secondary outcomes were evaluated by the voided volume, maximum urinary flow rate (Qmax ), and quality of life, as assessed by Barthel Index (BI) scale. In addition, adverse events were also recorded during the study period. All primary and secondary outcomes were measured at baseline, at the end of 8-week treatment, and 4-week follow-up. Results: At the end of 8-week treatment, the patients in the treatment group did not achieve better outcomes in PV-VRU ( P  = .66), voided volume ( P  = .59), Qmax ( P  = .53), and BI scores ( P  = .67), than patients in the control group. At the end of 4-week follow-up, there were also no significant differences regarding the PV-VRU ( P  = .42), voided volume ( P  = .71), Qmax ( P  = .24), and BI scores ( P  = .75) between 2 groups. No adverse events occurred in either group. Conclusions: In summary, the findings of this study showed that NMES therapy may not benefit patients with CUR following TBI.